Healthy Living Community Movement Policy as an Effort to Eradicate Poverty in Medan City - Thamrin, Husni; Pirandy, Gusti; Ritonga, Fajar Utama; Suriadi, Agus; Nasution, Mohammad Arif (PT FORMOSA CENDEKIA GLOBAL, 2024)
Poverty reduction efforts should also include improving access to health services and environmental conditions. Medan Mayor Regulation No. 61 of 2021 on Healthy Living Community Movement (GERMAS) aims to improve the quality of life through a healthy lifestyle and reduce healthcare costs. The GERMAS policy has been implemented to improve the quality of life. However, the challenge is to change people's behavior and implementing the GERMAS policy in Medan City is quite tricky. This study used a descriptive qualitative method combined with a literature review. Data collection strategies were obtained from observation and literature review. Data reduction, data presentation, and conclusion drawing were used as data analysis procedures. The results showed that the Medan City Government's GERMAS policy aims to increase productivity and reduce the financial burden of unhealthy living habits. The policy aims to reduce maternal mortality, improve nutrition, and alleviate poverty. However, its implementation is inefficient due to insufficient cross-sectoral coordination, limited resources, and low public awareness. To improve, the government should focus on innovation, community development, healthy lifestyles, and collaboration between government sectors.